2016
DOI: 10.7860/jcdr/2016/22705.8836
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Granuloma Secondary to Embolic Agent: A Case Report

Abstract: A 24-year-old female presented with weakness of left upper limb and an episode of generalised seizure. She had a history of right parieto-occipital Arteriovenous Malformation (AVM) which was embolised in four settings with different embolic agents (glue, polyvinyl alcohol). She had received Gamma Knife Surgery (GKS) for residual AVM. Post radiosurgical procedure, there was complete obliteration of AVM which was confirmed on angiography. However, she had developed an intracranial Space Occupying Lesion (SOL) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In this patient, Onyx and two more different embolic substances were used, thus making more difficult a precise definition of the etiopathogenesis. 6) A foreign body granuloma reaction to Onyx embolization for a congenital orbito-facial vascular malformation was also reported. The histopathological findings of this extracranial AVM included Onyx particles partially impacted in small vessels and numerous multinucleated giant cells that had phagocytosed the Onyx particles.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this patient, Onyx and two more different embolic substances were used, thus making more difficult a precise definition of the etiopathogenesis. 6) A foreign body granuloma reaction to Onyx embolization for a congenital orbito-facial vascular malformation was also reported. The histopathological findings of this extracranial AVM included Onyx particles partially impacted in small vessels and numerous multinucleated giant cells that had phagocytosed the Onyx particles.…”
Section: Discussionmentioning
confidence: 95%
“…4)6)8) Only one case report on a cerebral foreign body granuloma reaction to Onyx was found in the literature. 6) Murayama et al conducted a histopathological study in swine rete mirabile before Onyx introduction into the market. They demonstrated that Onyx generates a perivascular inflammatory reaction in subacute (18 days) and chronic (one to six months) stages with a granulomatous response characterized by the presence of epithelioid and multinucleated foreign body giant cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations